A proposed digitization plan for archival materials at the University of the Philippines Diliman University Archives and Records Division - Tan, Marie Eugenie B.; Arlante, Salvacion M. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2001)
The foremost aim of the study was to come up with a digitization plan specially catered to the preservation needs of the University Archives and Records Division of the University of the Philippines Diliman Main Library. The study was conducted in order to provide the UARD with an alternative to their preservation practices.
The researcher gathered data on the specific maintenance requirements of the UARD through a questionnaire completed by the librarians and library personnel. Results showed that UP publications such as the Philippine Collegian must be given utmost importance in digitization because these materials are quickly damaged. Other library resources to be digitized are the abstracts of theses/dissertations.
A number of challenges are to be faced by the project. One is the provision stated by the copyright law, another is the restriction set by the U.P. Administration which does not authorize the digitization of their special collection (papers of the Board of Regents and of the past U.P. Presidents). Extra finances have to be allotted for the procurement of equipment and staff-training.
Through this study, the researcher recommended the inclusion of online accessibility of the archival materials in future digitization plans and the digitization of other materials such as audio files.
Vita.
Thesis (Bachelor of Library and Information Science)
Keywords: Archival materials -- Digitization; University Archives and Records Division; University of the Philippines Diliman Main Library